2006
DOI: 10.1097/00042737-200605000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of coeliac serological tests: a prospective study

Abstract: Our study suggests that transglutaminase screening (using the IgA+/-IgG isotype) is a sensitive and specific alternative to endomysial antibody testing in the serological assessment of CD. On the basis of our findings, AGA antibody testing no longer appears to be an essential part of the diagnostic strategy for adult CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
72
0
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 29 publications
9
72
0
3
Order By: Relevance
“…The proportion of our subjects with histopathologically confirmed celiac disease is comparable to the results of a study by Reeves et al (7), but considerably higher than that reported by Hill et al (19).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The proportion of our subjects with histopathologically confirmed celiac disease is comparable to the results of a study by Reeves et al (7), but considerably higher than that reported by Hill et al (19).…”
Section: Discussionsupporting
confidence: 88%
“…Epidemiological data about celiac disease in Serbia are virtually non-existent. The age structure of our subjects was similar to those reported for Australian (7) and British (19) populations, but there were fewer women in our sample.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…CD is one of the most common gastrointestinal disorders, with a prevalence of 1:100-1:200 in the general population (1)(2)(3). The large increase in CD diagnosis over recent decades is in large part due to the availability of immunoassays with excellent diagnostic accuracy, such as the IgA anti-transglutaminase (anti-tTG) antibody assay (4)(5)(6)(7)(8). However, discordant data between adults and children have been reported as the anti-tTG assay is less accurate in very young patients and autoantibody levels can fluctuate (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The neoepitope screening assay detects antibodies to tTG, deamidated gliadin peptide and to the neoepitope and is thus the first assay used in our algorithm. This assay was able to provide earlier detection than the other tTG ELISA kits; 12,13 however, such cases may be interpreted as falsepositive cases by the first line screen. Applying the second-step screen with the tTG IgA and tTG IgA1IgG assays eliminated the false-positive results in many cases.…”
Section: Discussionmentioning
confidence: 99%